EXPLORING THE PATIENT SAFETY VIEWPOINTS OF SAUDI HEALTH ASSISTANTS, PHARMACY TECHNICIANS, DENTAL ASSISTANTS, RADIOLOGIC TECHNOLOGISTS, AND NURSING TECHHNICAINS: A MIXED METHODS INVESTIGATION - Fahad Rbaia Alanazi, Ahmad Nowairan M Aldhafeeri, Jasem Mohamad Afran Alshmeri, Nawaf Fadhel Alshammari, Khalid Ibrahim Aber Aldafiri, Mubarak Atiya Al-Anazi, (Chelonian Research Foundation, 2022)
Delivering safe, high quality healthcare free of preventable harm is an imperative priority across health systems. This convergent parallel mixed methods study aimed to explore the perspectives of 75 Saudi allied health techhnicains and professionals regarding patient safety in their educational and clinical settings. A survey and focus groups were conducted with health assistants, pharmacy technicians, dental assistants, radiologic technologists, and nursing techhnicains at 3 hospitals and 2 universities. Key quantitative results showed high ratings for teamwork and communication's vital importance for patient safety. Major qualitative themes emphasized needs for enhanced clinical training focused on safety competencies, empowering frontline personnel to speak up regarding risks, improving procedures and protocols, and optimizing use of technology/tools through standardization. Integrated findings provide critical insights from the lens of diverse allied health roles to guide multifaceted organizational and system-wide initiatives aimed at strengthening the patient safety culture across Saudi Arabian clinical learning and practice environments.